The influence of fairness on channel member relationship satisfaction: A case of Malaysian car dealers - Mohd Nor, Nor Azila; Perumal, Selvan; Hussin, Zolkafli (Society for Alliance, Fidelity & Advancement, 2011)
Undeniably, buyer-supplier relationship has become an important issue in today’s business -to-business environment.In business-to-business, dealers or marketing channels are increasingly emphasising relationships they have with their suppliers.Consistent with the increasing interest in buyer-supplier relationships, relationship satisfaction has become an important factor in relationship marketing and channel theory.Despite the assumption that relationship satisfaction influences buyer-supplier relationship, the factors that contribute to relationship satisfaction has not received much research attention.Using a survey method, this study investigates the influence of fairness on relationship satisfaction among 107 Malaysian car dealers. The findings suggest that perceived fairness has significant associations with relationship satisfaction.The results of this study will be of particular interest of practicing suppliers for maintaining relationship with dealers.